The CONLIT Dataset of Contemporary Literature. (11th October 2022) - Piper, Andrew
This dataset includes derived data on a collection of ca. 2, 700 books in English published between 2001–2021 and spanning 12 different genres. The data was manually collected to capture popular writing aimed at a range of different readerships across fiction (1, 934) and non-fiction (820). Genres include forms of cultural capital (bestsellers, prizewinners, elite book reviews), stylistic affinity (mysteries, science fiction, biography, etc.), and age-level (middle-grade and young adult). The dataset allows researchers to explore the effects of audience, genre, and instrumentality (i.e., fictionality) on the stylistic behavior of authors within the recent past across different classes of professionally published writing.